Kedudukan Putusan Peradilan Etik sebagai Keputusan Tata Usaha Negara: Studi Kasus Gugatan Hakim Konstitusi Anwar Usman - Febriyanto, Satrio (Jurnal Hukum & Pembangunan, 2026)
As an effort to concretize ethics, there is a process of formalizing ethics into a set of rules through a code of ethics. The code of ethics needs institutional enforcement instruments so that it can be effectively applied through ethical trials. Ethical courts, as institutions that adjudicate violations of the code of ethics, have the authority to issue decisions as a follow-up to cases of violations of the code of ethics that they handle. In carrying out its duties, ethical courts use ethical and moral analysis to assess the appropriateness of an action. This analytical approach differs from legal decisions based solely on regulations. This condition makes the positivization of ethics through legal adjudication dangerous to the substance of code of ethics violations that are problematic, as occurred in the case of Constitutional Court Judge Anwar Usman's code of ethics violation, which was adjudicated by the Jakarta Administrative Court. Through a doctrinal research method with a comparative approach, this paper aims to describe the position of ethical court decisions as objects of dispute in the Administrative Court. Based on the analysis conducted in this paper, ethical courts, in principle, have a different approach to handling cases than legal courts, a condition that creates a distortion in the decisions rendered.